COPYING OF TAKHMISH AL-QAWAFI IN THE TRADITION OF THE AMPEL ARAB COMMUNITY - Alindah, Lutfiyah; Indriyani, Jiphie Gilia; Aditoni, Agus (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
The old literary works develop through innovation. The reader is a copyist. The copyist responsed and interpreted the literary work of Takhmish al-Qawafi text. This paper revealing the copyist’s response in the Takhmish al-Qawafi copy text and classifying text as Islamic literature. Through the structure of the text and variations of the readings and spellings that exist in the two Takhmish al-Qawafi text, this text will be revealed the creation of copyist in the reception of the text. This research is philology descriptive. Through the reception analysis is noted that the aspect of structure texts have not differences because both of them have the same structure. Both of the texts consist the complete text, opening, content and closing. While in the contents of the text, the variations are not so obvious because the variations just only at the level of syakal, letters and dots. So, the message does not change significantly. While in the colophon, the level of copyist creation is very obvious because the disclosure in meaning level is different, but both of the mean is same. While the obvious creations are the lines surrounded the colophons that show the creativity of copying.